Biological and microbiological behavior of calcium aluminate cement-based blend for filling of bone defects - de Vasconcellos, Luana Marotta Reis [UNESP]; Camporês, Kaíke Lessa [UNESP]; de Alcântara Abdala, Julia Marinzeck; Vieira, Marilia Nanni [UNESP]; de Oliveira, Ivone Regina (Springer Nature, 2020)
Calcium aluminate cement (CAC) as a biomaterial has been evaluated for its physical, mechanical and biocompatibility properties. Furthermore, the application of CAC for bone repair is due to its composition and coefficient of thermal expansion, which is similar to that of human bone. Thus, the aim of this study was to evaluate compositions of CAC-based blends as substitutes for bone defects. Five compositions of blends (alumina, zirconia, hydroxyapatite, tricalcium phosphate, chitosan), in addition to the base cement consisting of homogeneous CAC were evaluated as a substitute for bone repair. Additionally, the monotypic biofilm formation was assessed. Creation of a monocortical bone defect was performed on the femurs of rats, which were randomly filled with the different materials. The polymethylmethacrylate (PMMA) group was used as a control. All the animals were euthanized 04 weeks after the surgery procedure. Subsequently, computerized microtomography, histological and histomorphometric analyses were performed to verify the bone repair. To evaluate the formation of biofilms, reference strains of Staphylococcus aureus, Streptococcus mutans and Pseudomonas aeruginosa were cultured on the samples, and the biofilm formed was quantified by the MTT method. In the microtomography and histomorphometry results, it was observed that the blends exhibited better results than the control group, with statistically significant differences (p < 0.05) for alumina and zirconia blends. In the biofilm formation, a statistical difference (p < 0.05) in general was observed between the alumina blends and the control group (p < 0.05). It was concluded that CAC-based blends with alumina and zirconia are promising for use in fillings for bone repair. [Figure not available: see fulltext.].